Nikephoros II Phokas and Warfare in the 10th-Century Byzantine World - Theotokis, Georgios,; Tsurtsumia, Mamuka, (History of Warfare ;, 2025)
This volume throws light not just on the military and on warfare during a period of increasing Byzantine military success and expansion, but it also draws on the latest in academic debate and examines afresh the varied aspects of different thematics regarding the reign of the emperor Nikephoros II Phokas. That includes military theory, tactics and equipment in the 10th century, 'war ideology' and the ideological justification of war, Byzantine society's attitudes to warfare, Nikephoros' approaches to domestic affairs and the Church, and the emperor's foreign policy. Contributors are Jesse S. Arlen, Gennadiy Baranov, Georgios Chatzelis, Jean-Claude Cheynet, Phoebe-Irene Georgiadi, Konstantinos Karatolios, Taxiarchis Kolias, Alexandru Madgearu, Lucas McMahon, Marco Miotto, Ioannis S. Sarantidis, Filip Schneider, Dimitrios Sidiropoulos, Denis Sullivan, Konstantinos Takirtakoglou, Georgios Theotokis, and Mamuka Tsurtsumia.